SOCIAL PROBLEMS OF ELDERLY PEOPLE IN ROMANIA (PANGEEA, 2025)
Elderly people live real dramas because of their exclusion from social and economic life, but mostly because on several occasions they are abandoned in their old age by their own children. Moreover, once they grow older these people start confronting various health problems and need the help of someone else almost permanently. Thus, they become dependent, experiencing strong feelings of frustration, insecurity, because of lack of control over their own lives, impatience, anger, when the care is inappropriate, guilt towards the caretaker. The activities which have taken place up to the present in favors of elderly people were sporadic and without results, and concerning abandoned, isolated, and sick old people, they were practically inexistent. The elderly has difficulties in maintaining normal living standards because of economic problems which led to the apparition of an aggravating state of poverty among them.
Keywords: elderly person; exclusion; problems; social